A Metamaterial Emitter for Highly Efficient Radiative Cooling. Issue 8 (2nd April 2015) - Hossain, Md Muntasir; Jia, Baohua; Gu, Min
<x xml:space="preserve">Abstract</x> A metamaterial thermal emitter for highly efficient radiative cooling is demonstrated. The emitter selectively radiates within the atmospheric transparency window and minimizes absorption of atmospheric radiation outside the transparency window. Exploiting its intriguing radiative properties, the emitter has the ability to deliver a remarkably high cooling power of more than 100 W m−2 and to cool down 12 °C below the ambient temperature.